Reaction and system modelling for Pb and PbO₂ electrodes - Varela, Francisco Eduardo (1997)
Reaction models for the metal dissolution, active–passive transition and passive layer electro- reduction processes taking place during discharge/charge of the electrode active materials in the lead/sulphuric acid system are discussed. Reaction and system modelling can be evaluated on the base of results obtained from steady-state polarization, potentiostatic pulses, single (STPS) and repetitive (RTPS) triangular potential sweeps, modulated voltammetry, complex voltammetry combined with potentiostatic steps, and electrochemical impedance spectroscopy (EIS), using rotating ring Pb-disc Pb-electrode assemblies, as well as scanning electron microscopy (SEM). Data analysis derived from transient electrochemical techniques employing both parametric identification procedures, nonlinear fit routines and computer simulations has been interpreted in terms of appropriate nucleation and growth models for the formation of new phases, in which the characteristics and properties of the compounds generated on electrode surface exhibit a remarkable dependence on the corresponding operational potential.